A randomized controlled trial of a videoconferencing smoking cessation intervention for Korean American women: preliminary findings - Kim SS; Sitthisongkram S; Bernstein K; Fang H; Choi WS; Ziedonis D (Dove Medical Press, 2016)
Sun S Kim,1 Somporn Sitthisongkram,1 Kunsook Bernstein,2 Hua Fang,3 Won S Choi,4 Douglas Ziedonis5 1Department of Nursing, College of Nursing and Health Sciences, University of Massachusetts Boston, Boston, MA, 2Hunter-Bellevue School of Nursing, Hunter College, City University of New York, New York, NY, 3Department of Quantitative Health Sciences, University of Massachusetts Medical School, Worcester, MA, 4Department of Preventive Medicine and Public Health, University of Kansas Medical Center, Kansas City, KS, 5Department of Psychiatry, University of Massachusetts Medical School, Worcester, MA, USA Introduction: Korean women are reluctant to pursue in-person smoking cessation treatment due to stigma attached to women smokers and prefer treatment such as telephone and online smoking cessation programs that they can access secretively at home. However, there is some evidence that face-to-face interaction is the most helpful intervention component for them to quit smoking.Methods: This study is a pilot clinical trial that examined the acceptability and feasibility of a videoconferencing smoking cessation intervention for Korean American women and compared its preliminary efficacy with a telephone-based intervention. Women of Korean ethnicity were recruited nationwide in the United States and randomly assigned at a ratio of 1:1 to either a video arm or a telephone arm. Both arms received eight 30-minute weekly individualized counseling sessions of a deep cultural smoking cessation intervention and nicotine patches for 8 weeks. Participants were followed over 3 months from the quit day. Results: The videoconferencing intervention was acceptable and feasible for Korean women aged <50 years, whereas it was not for older women. Self-reported abstinence was high at 67% and 48% for the video and telephone arm at 1 month post-quit, respectively. The rates declined to 33% for the video arm and 28% for the telephone arm at 3 months post-quit when salivary cotinine test was performed. Conclusion: Findings support that both videoconferencing and telephone counseling can be effective, and personal preference is likely an important factor in treatment matching. The deep cultural smoking cessation intervention may account for the outcomes of telephone counseling being better than prior studies in the literature for Korean women. Keywords: smoking cessation, women, videoconferencing, nicotine, remote biochemical validation, Asian American